FcγRIIB-mediated inhibition of T-cell receptor signal transduction involves the phosphorylation of SH2-containing inositol 5-phosphatase (SHIP), dephosphorylation of the linker of activated T-cells (LAT) and inhibition of calcium mobilization. (November 2001) - Jensen, W. A.; Marschner, S.; Ott, V. L.; Cambier, J. C.
Abstract : The low-affinity receptor for immunoglobulin G, FcγRIIB, is expressed on most B-cells and on immature and activated mature T-cells. Co-aggregation of FcγRIIB with the B-cell antigen receptor (BCR) leads to attenuation of BCR-induced blastogenesis and cell proliferation via inhibition of p21 ras, phosphatidylinositol 3-kinase (PI3-K) and phospholipase Cγ (PLCγ) activation. These effects are mediated, at least in part, by the recruitment of SH2-containing protein tyrosine phosphatase-1 (SHP-1) and -2 (SHP-2) and SH2-containing inositol 5-phosphatase(SHIP). In this report, we demonstrate that FcγRIIB co-aggregation with the T-cell antigen receptor (TCR), which may occur when T-cells recognize antibody-coated target cells, leads to inhibition of TCR-induced phosphorylation of the linker of activated T-cells (LAT). When phosphorylated, LAT functions as an adapter molecule and recruits PI3-K. Additionally, we demonstrate that PI3-K is required for TCR-induced Ca 2+ mobilization. Together, these data suggest that FcγRIIB may inhibit TCR-mediated Ca 2+ mobilization, in part via inhibition of LAT phosphorylation and subsequent inhibition of PI3-K activation. A similar mechanism has been described in B-cells, where FcγRIIB co-aggregation with the BCR leads to inhibition of PI3-K activity via dephosphorylation of CD19. It is likely that, in both cell types, levels of PtdIns(3, 4, 5)P3 are additionally modulated via the enzymic activity of SHIP.